Here's the question you clicked on:
mckayla_04
what is (3 raidcal 5 +1) (2 radical 5 -3) ??
answers;; 33 - 11 raidcal 5 27 - 7 radical 5 33 - 11 radical 5 27 - 7 raidcal 5
can you multiply it out?
|dw:1333196161836:dw|
so the problem is simplifying? ok, what do you have so far?
\[(3\sqrt{5}+1)(2\sqrt{5}-3)\]\[=(3\sqrt{5})(2\sqrt{5}-3)+(1)(2\sqrt{5}-3)\]\[=(3\sqrt{5})(2\sqrt{5})-(3\sqrt{5})(3)+(2\sqrt{5}-3)\]\[=(3\times 2\times\sqrt{5^2})-(3\times 3\sqrt{5}) + 2\sqrt{5}-3\]\[=6\times 5-9\sqrt{5} + 2\sqrt{5}-3\]\[=30-3-9\sqrt{5} + 2\sqrt{5}\] Can you simplify it?
good ques but i cant answer it !! too sorry !!